Effekter av gödsling i äldre tallbestånd på renbetesväxter i fält- och bottenskikt - Werndin, Lisa (SLU/Dept. of Forest Ecology and Management, 2007)
Reindeer husbandry and Forestry are both area related industries and will in big extent use the same lands. Conflicts often arise because of that the industries have different interests. Many of the activities done by the forestry influences the reindeer husbandry in an undesirable way, simultaneously as the reindeer husbandry activities can have negative consequences for the forestry. One such forestry activity is fertilization. It was during the 1960´s forest fertilization began to be practiced and the reason was that the increase in growth that the fertilization gave could be able to cover for the future shortage in wood many feared. During the 1970´s when the fertilizing activities were most intensive about 200 000 ha was fertilized annually. The uncertainty about which consequences N-fertilization would have on the ecosystems gave a decrease in fertilizing activities, and in the beginning of the 21th century only 30 000 ha was fertilized every year. Much research has been concentrated to questions concerning fertilizing and the knowledge about the production effects and the consequences on the environment has improved. This in combination with the great demand of wood and high woodprices has again made it interesting to fertilize the forest, to make it possible to take out larger volumes from the forests. The aim of this study was to evaluate the consequences intensive forest fertilization in older pine stands have on species in field- and bottom layer, mainly the species that is of importance for the reindeer and the reindeer husbandry. The study was carried out in an area 10 km SE of Åsele where SCA Forest Products since 1982 is pursuing an experiment concerning intensive forest fertilizing in older pine stands (Pinus sylvestris). The intention with the original experiment was to study how different fertilizing intervals influence growth plus to investigate whether an intensive fertilizing program can evoke shortage in boron and/or other micronutrients. When the experiment was constructed the stand ...